The efficiency of various doses of topical isosorbide dinitrate in the treatment of chronic anal fissure and the long-term results: A prospective, randomized and controlled clinical trial - Kirkil, Cuneyt; Aygen, Erhan; Dogru, Osman; Selim, Yavuz; Ayten, Refik; Camci, Cemalettin; Gogebakan, Ozkan (Aves, 2012)
Background/aims: In recent years, numerous studies have reported that the application of topical isosorbide dinitrate can cause fissure recovery with the relaxation of the internal anal sphincter. However, there is no consensus about the dose or duration of the drugs to be applied. In addition, long-term results of the patients with chronic anal fissure treated with nitrate-containing compounds are unknown. In this study, the goal was to investigate the effects of various doses of isosorbide dinitrate on chronic anal fissure and their long-term effects. Methods: Seventy-five sequential patients with chronic anal fissure were divided into three groups. Only symptomatic treatments were applied to patients in the first group (n=15). The patients in second and third groups (n=30 each) were treated with topical isosorbide dinitrate 5% and 10%, respectively. The patients were examined three times at 20-day intervals. Five years later, 44 patients who were responsive to treatment were contacted by telephone. Results: The rate of full response in the 10% isosorbide dinitrate group was statistically higher than of the 5% isosorbide dinitrate group on the 20th day (53.3% us. 26.7%, p<0.05). However, the rate of full response did not differ between these groups on the 40th and 60th days (63.3% and 70% vs. 56.7% and 63.3%, p>0.05). Five years later, 52.3% of patients who were responsive to treatment had a symptomatic relapse. Conclusions: Topical isosorbide dinitrate is a good alternative therapy to protect internal anal sphincter in the treatment of chronic anal fissure. However, the recurrence rates are high in the long-term.
Keywords: Chronic anal fissure; isosorbide dinitrate; internal anal sphincter